cytological and cytomorphological comparative study of oral mucosa in diabetes mellitus and nondiabetics in Misan Governorate. - Noor Saeed Aneed / Ali Khalaf Ali / Maitham Abdel Kazem Daragh ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This study compared type I and type II diabetic patients with a healthy control group using microscopic qualitative analysis of oral epithelial cytological smears in the possible early phase of diabetes. The cheek, ventral tongue mucosa, buccal, and palate smears were used for the superficial and profound cytological examination of the oral alterations. The type, duration, and consequences of diabetes were linked with cytological alterations of the oral cell population stained with PAP stain (Papanicolaou), PAS (Periodic acid-Schiff), hemotoxylin, and eosin. To detect changes, the experiment was conducted on 100 samples: 50 healthy people, 50 people with type I diabetes, and type II diabetes. They were taken from different areas, stained, and then examined with an optical microscope